KNOWING YOUR POTENTIAL IN APPLYING EARLY ENTREPRENEURIAL ACTIVITIES - Indrayani; Angelina Eleonora Rumengan; Muhammad Gita Indrawan; Suhana; Azizul Huda (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Entrepreneurship is an activity that creates new jobs. This Community Partnership Program offers several approach methods that can help attract enthusiasm for studying, namely by carrying out socialization methods about early entrepreneurship. This can later become motivation and provision for friends at the orphanage so they can start building a business from an early age. Entrepreneurship training activities for the community at the Al-Jufri Orphanage are generally going well, this is shown by the growing spirit, motivation and creativity of the Al-Jufri Orphanage to explore potential business ideas and the creation of new business plans that will be developed by the orphanage. Al-Jufri's care.